A qualitative exploration of patients' experiences, needs and expectations regarding online access to their primary care record. Issue 3 (11th March 2021) - McMillan, Brian; Davidge, Gail; Brown, Lindsey; Lyons, Moira; Atherton, Helen; Goulding, Rebecca; Mold, Freda; Morris, Rebecca L; Sanders, Caroline
Abstract : Objectives: Primary care records have traditionally served the needs and demands of clinicians rather than those of the patient. In England, general practices must promote and offer registered patients online access to their primary care record, and research has shown benefits to both patients and clinicians of doing so. Despite this, we know little about patients' needs and expectations regarding online access to their record. This study explored what patients and carers want from online access to their electronic primary care health record, their experiences of using it, how they would like to interact with their record and what support they may need. Design: Focus groups and semistructured interviews using purposive sampling to achieve a good sociodemographic spread. Interviews were digitally audiorecorded, transcribed and coded using an established thematic approach. Setting: Focus groups and interviews were conducted in community settings in the UK. Participants: Fifty-four individuals who were either eligible for the National Health Service Health Check, living with more than one long-term condition or caring for someone else. Results: Participants views regarding online access were categorised into four main themes: awareness, capabilities, consequences and inevitability. Participants felt online access should be better promoted, and suggested a number of additional functions, such as better integration with other parts of the healthcare system. It was felt that online access could improve quality of care (eg, through increased transparency) but also have potential negative consequences (eg, by replacing face to face contact). A move towards more online records access was considered inevitable, but participants noted a need for additional support and training in using the online record, especially to ensure that health inequalities are not exacerbated. Conclusions: Discussions with patients and carers about their views of accessing online records have provided useful insights into future directions and potential improvements for this service.